PRINSIP SYURA DALAM PENGAMBILAN KEPUTUSAN KEPEMIMPINAN BIROKRASI PADA LEMBAGA PENDIDIKAN ISLAM - Fauziah, Hamidatul Afifati; Thohir, Muhammad (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to analyze the application of the principle of shura in bureaucratic leadership decision-making in Islamic educational institutions. The main objective of this study is to examine how the principle of shura can be applied in the context of bureaucratic leadership in educational institutions, as well as to identify the challenges faced in the implementation process. This study uses a qualitative approach with library research, which was conducted by analyzing various literature related to shura, decision-making in bureaucracy, and Islamic educational leadership. The results of the study show that the application of the principle of shura in decision-making can increase the legitimacy of decisions, strengthen the participation of members of the institution, and produce more inclusive and fair policies. However, the biggest challenges found are resistance to change in the established bureaucratic structure and limitations in creating space for effective deliberation. The novelty of this research lies in the integration of the principle of shura in bureaucratic leadership in Islamic educational institutions, which has been discussed more in the context of government and political leadership. This research is expected to make a significant contribution to developing a more participatory and Islamic values-based model of educational leadership.